Formation of charge and spin ordering in strongly correlated electron systems - Čenčariková, H.; Farkašovský, P. (Condensed Matter Physics, 2011)
In this review we present results of our theoretical study of charge and spin ordering in strongly correlated electron systems obtained within various generalizations of the Falicov-Kimball model. The primary goal of this study was to identify crucial interactions that lead to the stabilization of various types of charge ordering in these systems, like the axial striped ordering, diagonal striped ordering, phase-separated ordering, phase-segregated ordering, etc. Among the major interactions that come into account, we have examined the effect of local Coulomb interaction between localized and itinerant electrons, long-range and correlated hopping of itinerant electrons, long-range Coulomb interaction between localized and itinerant electrons, local Coulomb interaction between itinerant electrons, local Coulomb interaction between localized electrons, spin-dependent interaction between localized and itinerant electrons, both for zero and nonzero temperatures, as well as for doped and undoped systems. Finally, the relevance of resultant solutions for a description of rare-earth and transition-metal compounds is discussed.